Heroes and toilers : work as life in postwar North Korea, 1953-1961 - Kim, Cheehyung Harrison (New York : Columbia University Press, 2018)
Heroes and Toilers offers an unprecedented account of life and labor in postwar North Korea that looks at both governance and popular resistance. Cheehyung Harrison Kim traces the state's pursuit of progress through industrialism and examines how ordinary people challenged the state every step of the way.
Introduction: postwar North Korea: the era of work -- The historical concept of work -- Work as state practice -- Producing the everyday life of work -- The rhythm of everyday work, in six parts -- Vinalon city : industrialism as socialist everyday life -- Conclusion: The negation of work and other everyday maneuvers -- Notes -- Bibliography -- Index.
Includes bibliographical references and index.
Print version record and CIP data provided by publisher; resource not viewed.
JSTOR
Keywords: Work -- Social aspects -- Korea (North) -- History -- 20th century; Korea (North) -- Social life and customs -- 20th century; Industrial organization -- Korea (North); Industrial management -- Korea (North); Travail -- Aspect social -- Corée du Nord -- Histoire -- 20e siècle.; Industrie -- Organisation, contrôle, etc. -- Corée du Nord; Gestion d'entreprise -- Corée du Nord; 1900 - 1999.; HISTORY -- Asia -- China; HISTORY -- Asia -- Korea; Industrial management; Industrial organization; Manners and customs; Work -- Social aspects; Korea (North); 1900-1999; History